Statistical analysis of overlapping double ion energy dispersion events in the northern cusp - da Silva, D. E.; Chen, L. J.; Fuselier, S. A.; Petrinec, S. M.; Trattner, K. J.; Cucho-Padin, G.; Connor, H. K.; Burkholder, B. L.; Huntenburg, A. J. (Frontiers in Astronomy and Space Sciences, 2024)
This article presents a statistical analysis of overlapping double ion-energy dispersion events in the northern cusp (“double dispersion”). Double dispersion in either cusp is a phenomenon associated with multiple reconnections occurring on the dayside magnetosphere as a result of its constant interaction with the variable solar wind. Using observations from a low Earth orbiting (LEO) Defense Meteorological Satellite Program (DMSP) satellite, we analyze 138 dayside events selected by the automatic algorithm extended from our previous work. We conducted a correlation study between the number of detected double dispersion events and 1) the month of the year to analyze the seasonal response of the cusp, and 2) solar wind interplanetary magnetic field (IMF) components and clock/cone angles to investigate its relationship with magnetic reconnection. We found that dispersion events occur more frequently during the northern summer months (i.e., when the dipole is tilted Sunward) and when the By component of IMF is positive. In addition, we provide a machine-readable list of the events and the code used to automatically detect the events.